(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The Mid-Carboniferous boundary in the Aladað Unit of the Central Taurides, previously delineated on the basis of foraminifers, is now further recognizable on the basis of conodonts. Latest Serpukhovian conodonts are assigned to the Rhachistognathus muricatus Zone, whereas the early Bashkirian forms correspond to the Declinognathodus inaequalis - Declinognathodus noduliferus Zone. Conodont assemblages discovered in the Taurides are comparable to those described from Mid-Carboniferous boundary sections in North America, Japan, southern Urals, southern China, Ukraine and Uzbekistan. The Mid-Carboniferous boundary is located at a horizon marked by the first appearance of Declinognathodus inaequalis, just above the last appearance of the conodont Gnathodus girtyi simplex. This horizon coincides with the boundary indicated by foraminiferal data.